Antibacterial and immunogenic behavior of silver coatings on additively manufactured porous titanium. (November 2018) - Croes, M.; Bakhshandeh, S.; van Hengel, I.A.J.; Lietaert, K.; van Kessel, K.P.M.; Pouran, B.; van der Wal, B.C.H.; Vogely, H.C.; Van Hecke, W.; Fluit, A.C.; Boel, C.H.E.; Alblas, J.; et al.
Graphical abstract: Abstract: Implant-associated infections (IAI) are often recurrent, expensive to treat, and associated with high rates of morbidity, if not mortality. We biofunctionalized the surface of additively manufactured volume-porous titanium implants using electrophoretic deposition (EPD) as a way to eliminate the peri-operative bacterial load and prevent IAI. Chitosan-based (Ch) coatings were incorporated with different concentrations of silver (Ag) nanoparticles or vancomycin. A full-scale in vitro and in vivo study was then performed to evaluate the antibacterial, immunogenic, and osteogenic activity of the developed implants. In vitro, Ch + vancomycin or Ch + Ag coatings completely eliminated, or reduced the number of planktonic and adherent Staphylococcus aureus by up to 4 orders of magnitude, respectively. In an in vivo tibia intramedullary implant model, Ch + Ag coatings caused no adverse immune or bone response under aseptic conditions. Following Staphylococcus aureus inoculation, Ch + vancomycin coatings reduced the implant infection rate as compared to chitosan-only coatings. Ch + Ag implants did not demonstrate antibacterial effects in vivo and even aggravated infection-mediated bone remodeling including increased osteoclast formation and inflammation-induced new bone formation. As an explanation for the poor antibacterial activity of Ch + Ag implants, it was found that antibacterial Ag concentrations were cytotoxic for neutrophils, and that non-toxic Ag concentrations diminished their phagocytic activity. This study shows the potential of EPD coating to biofunctionalize porous titanium implants with different antibacterial agents. Using this method, Ag-based coatings seem inferior to antibiotic coatings, as their adverse effects on the normal immune response could cancel the direct antibacterial effects of Ag nanoparticles. Statement of Significance: Implant-associated infections (IAI) are a clinical, societal, and economical burden. Surface biofunctionalization approaches can render complex metal implants with strong local antibacterial action. The antibacterial effects of inorganic materials such as silver nanoparticles (Ag NPs) are often highlighted under very confined conditions in vitro . As a novelty, this study also reports the antibacterial, immunogenic, and osteogenic activity of Ag NP-coated additively-manufactured titanium in vivo . Importantly, it was found that the developed coatings could impair the normal function of neutrophils, the most important phagocytic cells protecting us from IAI. Not surprisingly, the Ag NP-based coatings were outperformed by an antibiotic-based coating. This emphasizes the importance of also targeting implant immune-modulatory functions in future coating strategies against IAI.